Synthesis, photophysical characterization, relaxometric studies and molecular docking studies of gadolinium-free contrast agents for dual modal imaging - CuhaWijay Sathiyajith; Andrew J. Hallett; Peter G. Edwards (Results in Chemistry, 2022)
Three new EDTA-N, N’’ Bis(amides) ligands functionalized by luminophores (4-(aminomethyl)pyridine (L1) and 2-aminoanthraquinone (L2) and sulphonate (aminomethanesulfonic acid (L3)) on the amide side-arms (L1-L3) and their transition metal complexes (Mn (II), Cu (II) (except for L3), Zn (II)) were synthesized and characterized by analytical and spectroscopic techniques. The potential of L1-L3 to act as a dual-modal contrast agent for magnetic resonance imaging (MRI CA) was evaluated by measuring physicochemical properties such as (a) thermodynamic stability by measuring macroscopic protonation constants and stability constants with potentiometric titrations (b) R1 relaxivities by NMR relaxivity studies (c) spectrophotometric investigations. Comparative studies revealed Mn-L1 has performance comparable to the commercially available gadolinium-based contrast agents Magnevist® and Dotarem®. It is also higher than Teslascan® (manganese-based contrast agent, previously clinically approved and withdrawn from the market). Specifically, Mn-L1 exhibited relaxivity of 3.52 mM-1S-1 (at 30 MHz, 37 °C) as opposed to Teslascan® of 1.88 mM-1s−1(at 20 MHz, 37 °C). L1 also exhibited high overall stability constant for its Zn (II) complex (16.03), slightly higher than Teslascan® (15.1). Furthermore, the sharp break exhibited in the NMRD titration profile of L1 with Mn (II) indicated a 1:1 complex formation and substantiates a higher association constant. The photophysical characterization confirmed the ability of L1 and L2 to act as on–off type, fluorescent-based chemosensors for Cu (II). Time-resolved fluorescence investigations (TCSPC) indicated the potentiality of L1 for live-cell imaging. Unfortunately, while relaxivity studies on L2 were prevented by solubility issues at physiological pH, L3 exhibited poor complexation with Mn (II) and prevented further investigation. We also demonstrate through a structure-based virtual screening that L1 could act as a multi-target ligand to modulate the activity of two unrelated receptor proteins; Human aurora B kinase and Human serum albumin. Moreover, L1 exhibited a strong binding affinity for blood plasma protein, human serum albumin and this was relatively higher than FODIPIR, the ligand for Teslascan®.